Benign retroperitoneal cyst - important differential diagnosis of retroperitoneal mass - Kapil Rampal; Harkanwalpreet Kaur; Parampreet Singh Sandhu; Harinder Singh; Devinder Pal Singh (National Scientific Medical Center, 2023)
Retroperitoneal cyst is very rare clinical condition having incidence 1:5750 to 1:250,000. Most of the retroperitoneal lesions are asymptomatic. We are presenting a case of retroperitoneal cyst in a 65 years old female patient who presented with vague pressure symptoms. Exploratory laparotomy was performed. A large cystic right lumbar retroperitoneal mass displacing overstretched inferior vena cava, abdominal aorta and right psoas muscle seen intraoperative. Intact retroperitoneal cyst filled with its contents was removed. Large lesion as in our study cause abdominal pain, mass effect on kidney and major vessel consistent. We excised cyst in totocyst preserving vital structure to prevent spillage and avoid further recurrence which is consistent with standard literature. Retroperitoneal cysts are rare in incidence and asymptomatic. Due to silent nature and critical anatomy multidisciplinary approach is must for management of retroperitoneal cyst.